Genetic resistance in barley against Japanese soil-borne wheat mosaic virus functions in the roots - Okada, Kaori; Xu, Wenjing; Mishina, Kohei; Oono, Youko; Kato, Tsuneo; Namai, Kiyoshi; Komatsuda, Takao (Frontiers in Plant Science, 2023)
Infection by the Japanese soil-borne wheat mosaic virus (JSBWMV) can lead to substantial losses in the grain yield of barley and wheat crops. While genetically based resistance to this virus has been documented, its mechanistic basis remains obscure. In this study, the deployment of a quantitative PCR assay showed that the resistance acts directly against the virus rather than by inhibiting the colonization of the roots by the virus’ fungal vector Polymyxa graminis. In the susceptible barley cultivar (cv.) Tochinoibuki, the JSBWMV titre was maintained at a high level in the roots during the period December–April, and the virus was translocated from the root to the leaf from January onwards. In contrast, in the roots of both cv. Sukai Golden and cv. Haruna Nijo, the titre was retained at a low level, and translocation of the virus to the shoot was strongly suppressed throughout the host’s entire life cycle. The roots of wild barley (Hordeum vulgare ssp. spontaneum) accession H602 responded in the early stages of infection similarly to those of the resistant cultivated forms, but the host was unable to suppress the translocation of the virus to the shoot from March onwards. The virus titre in the root was presumed to have been restricted by the action of the gene product of Jmv1 (on chromosome 2H), while the stochastic nature of the infection was suppressed by the action of that of Jmv2 (on chromosome 3H), a gene harbored by cv. Sukai Golden but not by either cv. Haruna Nijo or accession H602.